2009
DOI: 10.4067/s0717-95022009000200036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ischemia/Reperfusion on ß Cells of Pancreas and Protective Effects of Melatonin Treatment

Abstract: Oxygen free radicals are considered to be important components involved in the pathophysiological tissue alterations observed during ischemia-reperfusion (I/R). In this study, we investigated the putative protective effects of melatonin treatment on pancreatic I/R injury. Sprague Dawley male rats were subjected to 30 min of pancreatic pedicle occlusion followed by 90 min reperfusion. Melatonin (10 mg/kg. s.c) was administrated 30 min prior to ischemia or I/R application. At the end of the reperfusion periods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
2
2
0
Order By: Relevance
“…Also, the treated group showed a significant decrease in lipid peroxidative enzymes ( Figures 1 A – B ) and a significant increase in antioxidant enzymes ( Figures 1 C – D ) compared to the I/R group in different periods. These results are in accordance with previous studies [ 21 , 22 ]. Abdollahzad et al .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Also, the treated group showed a significant decrease in lipid peroxidative enzymes ( Figures 1 A – B ) and a significant increase in antioxidant enzymes ( Figures 1 C – D ) compared to the I/R group in different periods. These results are in accordance with previous studies [ 21 , 22 ]. Abdollahzad et al .…”
Section: Discussionsupporting
confidence: 94%
“…However, the group treated with vitamin C showed significant histological improvement at different periods. These results are consistent with the findings of many previous studies [ 21 , 23 , 25 – 27 ] where the histological analysis showed that IR induced acute pancreatitis with the accumulation of inflammatory infiltrate, disruption of tissue structure, cell necrosis and hemorrhage. These conclude that the pancreas is highly susceptible to oxidative stress induced by IR injury, leading to the development of acute pancreatitis [ 21 , 23 ], and this damage can be prevented by antioxidants [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, I/R has been reported to induce a marked enhancement of oxidative stress in a variety of organs (Muñoz-Casares et al, 2006, Abogresha et al, 2016. Mechanistically, reperfusion and reoxygenation of tissues in the presence of hypoxanthine and xanthine oxidase lead to production of aggressive oxygen radicals (Marian et al, 2007;Yildirim et al, 2009).…”
Section: Discussionmentioning
confidence: 99%